The Effectiveness Of Pre-Trial Proceedings In Ensuring Control Mechanisms In The Investigation And Prosecution Process - Musa Darwin Pane; Sahat Maruli Tua Situmeang; Diah Pudjiastuti; Nur Ezan Rahmat (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Pretrial in the Indonesian criminal justice system aims to test whether or not the determination of suspects, detention, and confiscation by law enforcement officials is valid. However, the effectiveness of pretrial is often questioned, especially because the decision of a single judge in several cases is considered to violate the human rights of suspects and does not provide optimal legal certainty. This study aims to evaluate the effectiveness of a single judge in pretrial and to find alternative legal reforms that better guarantee the protection of human rights in the investigation and investigation stages. This research uses normative juridical method with statutory approach and case study on controversial pretrial decisions. The results showed that single judges in pretrial often have limitations in assessing the substance of the case as a whole, so that the resulting decisions are not always fair and can harm the suspect. In addition, there is legal uncertainty due to different interpretations in the determination of suspects. As a recommendation, it is necessary to reform the criminal justice system by removing the pretrial mechanism and replacing it with direct examination by judges in the main trial. In addition, restorative justice mechanisms and plea bargaining systems, which have been implemented in several countries, can be adapted to improve the efficiency of case resolution without compromising the protection of human rights. These reforms should also be accompanied by improvements to investigation and prosecution mechanisms to ensure greater transparency and accountability at every stage of the law.